Performance Study of a Wireless Mobile Ad Hoc Network with Orientation-Dependent Inter-Node Communication Links - Kostin, Alexander; Oz, Gurcu; Haci, Huseyin (IEEE, 2009)
A Petri-net-based simulation model of a wireless mobile ad hoc network is studied. The model includes a parameterized mobility model and a novel scheme of orientation-dependent inter-node communication links with random states. In simulation, three fundamental performance metrics - packet delivery rate, average number of hops and relative network traffic - are investigated under different combinations of model parameters.
24th International Symposium on Computer and Information Sciences -- SEP 14-16, 2009 -- Guzelyurt, CYPRUS
Keywords: mobile wireless ad hoc networks; mobility models; oriented links; simulation; petri nets